2012
DOI: 10.1111/j.1439-0523.2012.01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the linalool‐producing NES1 variant across diverse strawberry (Fragaria spp.) accessions

Abstract: With 4 figures and 3 tables Abstract Many volatile compounds have been shown to influence the flavour of strawberry (Fragaria spp.) fruit. A published study demonstrated that linalool, a critical flavour compound, is produced in cultivated F. × ananassa varieties owing to a truncated form of the NEROLIDOL SYNTHASE (NES) enzyme. The corresponding allele (FaNES1) features a 5′‐deletion that is detectable by PCR. Herein, we tested a broad set of strawberry genotypes to understand the origin of the allele and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…Before analysis, samples were held at 10 °C in a Peltier cooling tray attached to a MPS2 autosampler (Gerstel). All other volatile sampling and analysis methods were as previously described [ 23 ]. An authentic MA standard (Sigma Aldrich, St. Louis, MO, USA) was run under the same chromatographic conditions as fruit samples for verification of volatile identity.…”
Section: Methodsmentioning
confidence: 99%
“…Before analysis, samples were held at 10 °C in a Peltier cooling tray attached to a MPS2 autosampler (Gerstel). All other volatile sampling and analysis methods were as previously described [ 23 ]. An authentic MA standard (Sigma Aldrich, St. Louis, MO, USA) was run under the same chromatographic conditions as fruit samples for verification of volatile identity.…”
Section: Methodsmentioning
confidence: 99%
“…The terpenoid linalool appears as an exception with its pleasant freshflowery, citrus-like odor. Linalool was found in higher amounts in cultivars as also described by Chambers et al [5]. These authors postulated a mutation in the nerolidol synthase (FaNES1) occuring in octoploids (F. × ananassa) in contrast to the diploids (F. vesca).…”
Section: Diversity Of Volatile Patterns In One Harvest Seasonmentioning
confidence: 62%
“…It has an antimicrobial effect and it is present in the total pull of volatile organic compounds (VOCs) of many fruits and flowers. It is confirmed that linalool is the most important compound for strawberry flavor [37,38]. Furanone methyl ether typical of strawberries.…”
Section: 585mentioning
confidence: 72%